ПЕДАГОГИК-ПСИХОЛОГИК ФАНЛАРНИ ЎҚИТИШДА СУБЪЕКТГА ДОИР ПЕДАГОГИК ВАЗИЯТЛАРДАН ФОЙДАЛАНИШ - Курбаниязова, З.К. (SCIENCE and SOCIETY, 2022)
The article analyzes the issue of methodological support for the teaching of pedagogical and psychological sciences in higher education. It is stated that the creation of pedagogical conditions for the subject in the process of teaching the pedagogical and psychological sciences is one of the methods orienting future teachers towards the socialization of the pedagogical profession.
Keywords: education system; methodical support; pedagogical-psychological sciences; pedagogical situations; pedagogical situations on the subject